Duale Autonomie. Zur Rechtsgeschichte des Arbeitsmarktregimes - Gerd Bender (Rechtsgeschichte - Legal History)
The article deals with the legal history of the socalled dual system of industrial relations. In this constellation, which is typical for the German version of the labour market regime, the institutions of sectoral collective bargaining autonomy, based on the principle of association, and company autonomy, based on micro-corporatism, are linked. Coordination takes place through state law as well as the norm-generating practice of the actors involved.The article reconstructs the history of this dual autonomy, whose beginnings go back to the end of the 19th century. Particular emphasis is placed on norm-setting in the early Weimar Republic, which culminated in the Works Council Act of 1920. In its wake, the association model of collective bargaining autonomy became the centre of the labourmarket regime, and workplace autonomy was relegated to a secondary role. Macrocorporatist considerations, which also existed in the context of the constitutional discussion, took a back seat. The article does not provide a history of stability. At the end of the Weimar Republic, the dual system was the focus of a crisis of confidence and of institutions that heralded the end of the Weimar social model. The discourse at the time was heavily influenced by vehement demands that the need of companies for more flexibility be met by favouring company agreements over collective ones, but the decline of the republic put an end to these debates. Finally, the article looks at parallels that emerged later in the West German debate on the functional deficits of collective bargaining autonomy.